A new rule-based integrated decision making approach to container transshipment terminal selection. Issue 2 (17th February 2019) - Kadaifci, Cigdem; Asan, Umut; Serdarasan, Seyda; Arican, Umut
ABSTRACT: The choice of the port or terminal to perform transshipment operations is a critical decision for container transportation companies (i.e. shipping line companies). This choice is not only affected by transshipment costs but also by the location, infrastructure, equipment, and technologies of the alternative terminals. In this study, a rule-based integrated multi-criteria group decision making approach is proposed in order to support such complex decision processes which involve substantial uncertainties and subjectivities. The proposed approach involves simple mathematics and provides a flexible modeling approach close to human reasoning that is able to consider uncertain information and relationships of arbitrary complexity. To prioritize the sub-criteria affecting the choice of the most appropriate terminal and to assess alternatives with respect to these sub-criteria, the Analytic Hierarchy Process (AHP) based on absolute measurement is used. Then, to determine the most appropriate terminal, a Fuzzy Rule-Based System is developed, which adopts the scores of criteria (i.e. the total scores of sub-criteria) obtained by AHP as input. In order to demonstrate the applicability and effectiveness of the proposed approach, an application is presented for the choice of the most appropriate container transshipment port in Turkey for a shipping line company.